2009
DOI: 10.1096/fasebj.23.1_supplement.342.2
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and Obesity in Mexican Scholar Children

Abstract: ObjectiveThe aim of this study was to describe the prevalence of overweight and obesity (OW +O) and to assess its association with some risk factor in a probabilistic sample of Mexican scholars.MethodsInformation from 34,045 children (>6 y) extracted from the Mexican National Health in Publics Schools Survey in Mexico (ENSE‐2008) was included in the analysis. We examined body mass index (BMI) in relation to demographic variables, sweet beverages consumption, and physical activity.ResultsOur results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, NHANES 2011-2014 data indicate that Hispanic children and adolescents (2-19 years) have a lower caloric intake from sugar-sweetened beverages than their non-Hispanic white and non-Hispanic Black counterparts, but these beverages still contribute about 7.3% and 6.8% of the daily energy intake for boys and girls, respectively [17]. Furthermore, it has been reported that Hispanic adolescents have a high intake of snacks (>20% of their daily energy intake) [18] and ultra-processed foods (~64% of their daily energy intake) [19], both of which have been associated with obesity among Mexican-origin children [20,21]. All these dietary traits suggest an urgent need for strategies to improve diet and related behaviors in Hispanic adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, NHANES 2011-2014 data indicate that Hispanic children and adolescents (2-19 years) have a lower caloric intake from sugar-sweetened beverages than their non-Hispanic white and non-Hispanic Black counterparts, but these beverages still contribute about 7.3% and 6.8% of the daily energy intake for boys and girls, respectively [17]. Furthermore, it has been reported that Hispanic adolescents have a high intake of snacks (>20% of their daily energy intake) [18] and ultra-processed foods (~64% of their daily energy intake) [19], both of which have been associated with obesity among Mexican-origin children [20,21]. All these dietary traits suggest an urgent need for strategies to improve diet and related behaviors in Hispanic adolescents.…”
Section: Introductionmentioning
confidence: 99%